Peningkatan Kesehatan Masyarakat Melalui Inovasi Pengolahan Tanaman Apotek Hidup (Temulawak) Menjadi Puding Temulawak - Mike Elly Anitasari; Maula Nur Yuwanda; Tofik Yuliadi; Uzen Adhe Kusuma; Muhlisin Faozi; Syuvi Setiana; Luthfiya Nur Aini; Peti Dwi Astuti; Lianawati Lianawati; Rizal Cahya Putra; Ratna Indra Setyaningrum (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
Real Work Lectures (KKN) is a form of student service to society and is one part of the Tri Dharma of Higher Education. This KKN activity was carried out in Kalisemo Village, Loano District, Purworejo Regency. One of the work programs of KKN activities is socialization, here the KKN Team provides efforts to the community of Kalisemo Village, Loano District, Purworejo Regency in the form of transferring knowledge about the use of live apothecary plants (curcuma xanthorrhiza) by carrying out outreach activities to improve public health through innovations in processing live apothecary plants (curcuma xanthorrhiza) into ginger pudding. Pudding is a dessert that usually has a sweet taste, in contrast to curcuma which predominantly has a bitter and pungent taste. Using curcuma xanthorrhiza as pudding has various benefits, including increasing the body's immunity and increasing appetite. The target achieved from this activity is that the community is able to innovate in the use of live apothecary plants (curcuma xanthorrhiza) into a product that can increase entrepreneurial opportunities.